Parents` Perceptions of the Importance of Early Childhood Education District Pasar Rebo - Vinayastri, Amelia; Handayani, Septi (Indonesian Journal of Early Childhood Education Studies, 2017)
This study aims to look at the extent to which the parents perception of the importance of early childhood education (ECD) in Pasar Rebo. Subjects were 105 parents of children aged 3-6 years, both of which have got in early childhood education services or who have not received services in early childhood education or early childhood education service of others. This study uses a quantitative approach and the data collection methods used are questionnaires through the distribution of scores perception of parents using standard deviation formula. The results showed that parents' perceptions of the importance of early childhood education is very important category, 24%, 28% important, 48% fairly important, not important 0%, and 0% very important. The results of these studies indicate that parents do not fully understand that early childhood education is important as an important foundation of individual life in the future. Perception can direct the attitudes and behavior of parents so that when the perception of parents on the importance of positive early childhood education, parenting can be carried out in accordance with the stages of its development.